The experiences of diversion workers and volunteers in the implementation of the Youth Empowerment Scheme (YES) as a diversion programme in the Western Cape : an evaluation study - Arendse, Nicola (2007)
Includes bibliographical references.The aim of this study is to detennine the experiences of NICRO volunteers and diversion workers in the implementation of the YES programme as a diversion option in the Western Cape. This stems from the need to examine the current practice of diversion services in anticipation of the implementation of the Child Justice Bill (Bill 49 of 2002). The implementation of this Bill will have far-reaching repercussions for diversion service providers as it will mean an increase in demand for diversion services and the implementation of minimum standards for such services. A qualitative, evaluative research design was used for this cross-sectional study. The population of NICRO diversion workers in the Western Cape and a sample of volunteers from each of the NICRO offices in the Western Cape were included in the study. Individual interviews were conduded with the volunteers in their respective towns across the Western Cape using an interview schedule. Two focus group sessions were held with the diversion workers. Audio recordings were made of the interviews with volunteers and of the focus group sessions. The transcripts were then analysed for trends, themes and categories. The results were compiled and conclusions drawn. Volunteers and diversion workers generally experienced the YES programme as being positive and making a difference to the lives of participants. The volunteers derived personal satisfaction from facilitating programmes and receiving positive feedback from parents and participants alike. They faced a number of challenges, though, when facilitating the programme. Examples of such problems are with diversity of language, culture, age and educational levels within groups and the lack of co-operation of parents and resistant participants. These challenges volunteers faced with the assistance and guidance of the diversion workers and drawing on their own strengths and capacities